Training mid-level health cadres to improve health service delivery in rural Bangladesh - Rawal, Lal B.; Mahmud, Kawkab; Islam, Sheikh Md. S.; Mahumud, Rashidul A.; Nuruzaman, Md.; M. Ahmed, Syed (© 2016 Cambridge University Press, 2016)
This article was published in Primary Health Care Research and Development [© 2016 Cambridge University Press] and the definite version is available at: https://www.cambridge.org/core/services/aop-cambridge-core/content/view/S1463423616000104